Postmodern Illusions and the Challenges of African Theology: The Ecclesial Tactics of Resistance - Katongole, Emmanuel (Modern theology, 2000)
Contemporary African theological reflection has not sufficiently paid attention to the reality of postmodernism in general, its cultural expressions in particular. In this essay, I depict some of the illusions of a postmodern culture and how their power to shape the economic, cultural and imaginative visions of Africans remains one of the key theological challenges. Accordingly, the crucial test for African theology today will be whether it can generate enough critical skills and inspire new forms of community, which are capable of challenging, as well as offering alternatives to, the dangerous and playful nihilism of a postmodern culture.